Polyphosphate positive electrode material and preparation method thereof and secondary battery

By using a multi-layer cladding structure and carbon cladding design in lithium manganese iron phosphate positive electrode material, the problem of poor electrochemical performance of existing materials is solved, and higher compaction density, conductivity and electrochemical performance are achieved .

CN115036476BActive Publication Date: 2025-02-11SHENZHEN DYNANONIC CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210623029.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-02
Publication Date
2025-02-11
Estimated Expiration
2042-06-02

AI Technical Summary

Technical Problem

The electrochemical performance of existing lithium manganese iron phosphate cathode materials has caused their poor performance in energy storage and power battery applications.

Method used

The lithium manganese iron phosphate positive electrode material adopts a multi-layered coating structure. By covering the multi-layered lithium manganese iron phosphate coating layer on the inner core surface of the lithium manganese iron phosphate, and forming a carbon coating layer on the outer layer to form an "annual ring structure" to Improve the conductivity and compaction density of the material.

Benefits of technology

The compaction density, conductivity and electrochemical properties of lithium manganese iron phosphate cathode material have been significantly improved, and its energy density and cycling performance in secondary batteries have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115036476B_ABST
    Figure CN115036476B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of battery materials, and provides a polynary phosphate positive electrode material, the polynary phosphate positive electrode material comprises a lithium iron manganese phosphate composite particle and a carbon coating layer coated on the surface of the lithium iron manganese phosphate composite particle, the lithium iron manganese phosphate composite particle comprises a lithium iron manganese phosphate core and N layers of lithium iron manganese phosphate coating layers coated on the surface of the lithium iron manganese phosphate core; wherein the manganese-iron molar ratio of the lithium iron manganese phosphate in the lithium iron manganese phosphate core and each layer of the lithium iron manganese phosphate coating layer increases radially from inside to outside; the particle size of the lithium iron manganese phosphate particles in the lithium iron manganese phosphate core and each layer of the lithium iron manganese phosphate coating layer decreases radially from inside to outside. The lithium iron manganese phosphate composite particles contained in the polynary phosphate positive electrode material provided in the present application are "annual ring structures", and lithium iron manganese phosphate particles of different particle sizes are synthesized into a dense composite particle, which not only increases the particle size of the lithium iron manganese phosphate particles, but also significantly improves the compaction density of the internal filling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of battery materials, and in particular relates to a polyphosphate positive electrode material, a preparation method thereof, and a secondary battery. Background Art

[0002] Lithium-ion battery is an energy storage device that is widely used in the field of energy storage, power batteries and portable electronic devices. Lithium-ion batteries have advantages such as high operating voltage, low self-discharge and good safety. Lithium-ion batteries are mainly composed of positive electrode materials, negative electrode materials, electrolytes, diaphragms and casings. The positive electrode materials mainly include lithium cobalt oxide, lithium manganese oxide, nickel-manganese binary system, nickel-cobalt-manganese ternary system, nickel-cobalt-aluminum ternary system, lithium iron phosphate, lithium manganese iron phosphate, etc. Among them, lithium iron phosphate LiFePO4 has the advantages of low cost, high safety and good cycle life. Lithium manganese iron phosphate (LMFP, LiMn 1- x Fe x PO4) is developed on the basis of lithium iron phosphate modification. It is a solid solution material composed of lithium iron phosphate and lithium manganese phosphate. It has similar properties to lithium iron phosphate and lithium manganese phosphate, and has good thermal stability and chemical stability. Compared with lithium iron phosphate, lithium manganese iron phosphate has a higher voltage platform. The voltage of lithium manganese iron phosphate can reach about 4.1V, while that of lithium iron phosphate is about 3.4-3.5V. The two have the same theoretical gram capacity. Because the voltage is higher, the theoretical energy density of lithium manganese iron phosphate is 15-20% higher than that of lithium iron phosphate under the same conditions. At the same time, the electrical conductivity and lithium ion conductivity are improved compared with lithium manganese phosphate, and it is a positive electrode material that deserves great attention. However, the conductivity of a single lithium manganese iron phosphate material is very poor, and pure lithium manganese iron phosphate is almost an insulator, making it difficult to give full play to the electrochemical properties of the material.

[0003] The existing method can improve the conductivity of the material to a certain extent by using carbon coating, but the conductivity of the material is still very poor and the electrochemical performance of the material cannot be fully utilized. The preparation method of the lithium manganese iron phosphate positive electrode material with a multi-layer coating structure includes the steps of: mixing a manganese source, a phosphorus source, an iron source, a lithium source, a carbon source and a compound of a doping element to obtain a first mixture; pre-calcining the first mixture under different sintering temperature curves and a protective atmosphere to obtain precursors with different particle sizes; using a coating technology to sequentially coat the precursors according to the particle size from small to large to obtain a second mixture; calcining the second mixture under a protective atmosphere to obtain a lithium manganese iron phosphate with a multi-layer coating structure.

[0004] However, the existing preparation method uses pure substances to prepare lithium manganese iron phosphate. Due to the expensive raw materials, the preparation cost is high and it is difficult to achieve industrial production. In addition, the first mixture with the same manganese iron molar ratio is sintered at different temperatures to form precursors with different particle sizes. Although the compaction effect is improved, it is difficult to release the electrochemical properties of the lithium manganese iron phosphate material, which limits its application. Summary of the invention

[0005] The purpose of the present application is to provide a polyphosphate positive electrode material and a preparation method thereof and a secondary battery, aiming to solve the problem of poor electrochemical performance of existing lithium manganese iron phosphate positive electrode materials.

[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0007] In a first aspect, the present application provides a polyphosphate positive electrode material, the polyphosphate positive electrode material comprising a lithium iron manganese phosphate composite particle and a carbon coating layer coated on the surface of the lithium iron manganese phosphate composite particle, the lithium iron manganese phosphate composite particle comprising a lithium iron manganese phosphate core and an N-layer lithium iron manganese phosphate coating layer coated on the surface of the lithium iron manganese phosphate core;

[0008] Among them, the molar ratio of manganese to iron in the lithium iron manganese phosphate core and each layer of the lithium iron manganese phosphate coating increases radially from the inside to the outside; the particle size of the lithium iron manganese phosphate particles in the lithium iron manganese phosphate core and each layer of the lithium iron manganese phosphate coating decreases radially from the inside to the outside, and N is an integer greater than or equal to 1.

[0009] In a second aspect, the present application provides a method for preparing a polyphosphate positive electrode material, comprising the following steps:

[0010] preparing an ferromanganese phosphate core, and coating the surface of the ferromanganese phosphate core with N layers of ferromanganese phosphate coating layers to obtain ferromanganese phosphate composite particles;

[0011] The manganese iron phosphate composite particles and the lithium source are mixed and dissolved and reacted, and then dried to obtain manganese iron lithium phosphate composite particles;

[0012] A carbon coating layer is coated on the surface of lithium manganese iron phosphate composite particles to obtain a polyphosphate positive electrode material.

[0013] In a third aspect, the present application provides a secondary battery, the positive electrode material of which contains the polyphosphate positive electrode material provided in the present application, or contains the polyphosphate positive electrode material prepared by the preparation method provided in the present application.

[0014] Compared with the prior art, this application has the following beneficial effects:

[0015] The first aspect of the present application provides a multi-phosphate positive electrode material. On the one hand, the lithium iron manganese phosphate composite particles contained in the multi-phosphate positive electrode material include a lithium iron manganese phosphate core and a multi-layer lithium iron manganese phosphate coating layer, and the manganese-iron molar ratio of the core and each layer of the lithium iron manganese phosphate particles increases radially from the inside to the outside, and the particle size of the core and each layer of the lithium iron manganese phosphate particles decreases radially from the inside to the outside. This "annual ring structure" can not only increase the particle size of the lithium iron manganese phosphate particles and improve the compaction density of the positive electrode material, but also synthesize lithium iron manganese phosphate particles of different particle sizes into a dense composite particle, which can significantly improve the internal filling density of the composite particle, thereby further improving the compaction density of the positive electrode material; the manganese-iron molar ratio of the lithium iron manganese phosphate of each layer increases radially from the inside to the outside, that is, the lithium iron manganese phosphate with high manganese content and poor conductivity is placed in the outer layer of the composite particle, which can shorten the transmission distance of lithium ions and improve the conductivity. On the other hand, the carbon coating contained in the polyphosphate positive electrode material can further improve the conductivity of the lithium iron manganese phosphate particles, thereby improving the electrochemical performance of the polyphosphate positive electrode material. Therefore, the lithium iron manganese phosphate positive electrode material of the present application has high compaction density, good structural stability, good conductivity, and excellent electrochemical performance and cycle performance.

[0016] The preparation method of the polynary phosphate positive electrode material provided in the second aspect of the present application, first prepares the ferromanganese phosphate kernel, and coats the surface of the ferromanganese phosphate kernel with N layers of ferromanganese phosphate coating to form ferromanganese phosphate composite particles, and by means of multi-layer coating, the particle size of the ferromanganese phosphate lithium composite particles can be increased, and the compaction density and conductivity of the ferromanganese phosphate lithium positive electrode material can be improved. Then the ferromanganese phosphate composite particles and the lithium source are mixed and dissolved, so that the ferromanganese phosphate composite particles and the lithium source are reacted in a solution state, which can not only reduce the difficulty of synthesis, but also reduce the required reaction temperature. At the same time, the reaction is more sufficient, the product conversion rate is high, and the obtained ferromanganese phosphate lithium composite particles have good uniformity, so that the stability and cycle performance of the ferromanganese phosphate lithium are better. In addition, the present application is to coat the surface of the ferromanganese phosphate kernel with N layers of ferromanganese phosphate coating to form ferromanganese phosphate composite particles, and then synthesize with the lithium source to form ferromanganese phosphate lithium composite particles, which can further improve the compactness, compaction density, structural stability, etc. of the composite particles compared with the ferromanganese phosphate lithium particles directly formed by sintering the ferromanganese phosphate particles and the lithium source. Finally, a carbon coating layer is coated on the surface of the lithium manganese iron phosphate composite particles to further improve the conductivity of the lithium manganese iron phosphate positive electrode material, thereby further improving the electrochemical performance and cycle performance. In addition, the preparation method is simple in process, high in efficiency, low in cost, and suitable for industrial large-scale production.

[0017] The secondary battery provided in the third aspect of the present application contains the polyphosphate positive electrode material of the present application. The polyphosphate positive electrode material has electrochemical properties such as high energy density, electrical conductivity, compaction density, safety, and stability, thereby improving the electrochemical performance of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0019] Figure 1 It is a preparation flow chart of the method for preparing the polyphosphate positive electrode material provided in the embodiment of the present application. DETAILED DESCRIPTION

[0020] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0021] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0022] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0023] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0024] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0025] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0026] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0027] In a first aspect, an embodiment of the present application provides a polyphosphate positive electrode material, the positive electrode material comprising a lithium iron manganese phosphate composite particle and a carbon coating layer coated on the surface of the lithium iron manganese phosphate composite particle, the lithium iron manganese phosphate composite particle comprising a lithium iron manganese phosphate core and an N-layer lithium iron manganese phosphate coating layer coated on the surface of the lithium iron manganese phosphate core;

[0028] Among them, the molar ratio of manganese to iron in the lithium iron manganese phosphate core and each layer of the lithium iron manganese phosphate coating increases radially from the inside to the outside; the particle size of the lithium iron manganese phosphate particles in the lithium iron manganese phosphate core and each layer of the lithium iron manganese phosphate coating decreases radially from the inside to the outside, and N is an integer greater than or equal to 1.

[0029] The polyphosphate positive electrode material provided in the embodiment of the present application, on the one hand, the lithium iron manganese phosphate composite particles contained in the polyphosphate positive electrode material include a lithium iron manganese phosphate core and a multi-layer lithium iron manganese phosphate coating layer, and the manganese-iron molar ratio of the lithium iron manganese phosphate particles of the core and each layer increases radially from the inside to the outside, and the particle size of the lithium iron manganese phosphate particles of the core and each layer decreases radially from the inside to the outside. This "annual ring structure" can not only increase the particle size of the lithium iron manganese phosphate particles and improve the compaction density of the polyphosphate positive electrode material, but also synthesize lithium iron manganese phosphate particles of different particle sizes into a dense composite particle, which can significantly improve the density of the internal filling of the composite particle, thereby further improving the compaction density of the polyphosphate positive electrode material; the manganese-iron molar ratio of the lithium iron manganese phosphate of each layer increases radially from the inside to the outside, that is, the lithium iron manganese phosphate with high manganese content and poor conductivity is placed in the outer layer of the composite particle, which can shorten the transmission distance of lithium ions and improve the conductivity. On the other hand, the carbon coating contained in the polyphosphate positive electrode material can further improve the conductivity of the lithium iron manganese phosphate particles, thereby improving the electrochemical performance of the polyphosphate positive electrode material. Therefore, the lithium iron manganese phosphate positive electrode material of the present application has high compaction density, good structural stability, good conductivity, and excellent electrochemical performance and cycle performance.

[0030] In an embodiment, the number of layers of the lithium iron manganese phosphate coating layer N=6-10. Within the range of the number of layers of the lithium iron manganese phosphate coating layer contained in the lithium iron manganese phosphate composite particles provided in this embodiment, the particle size, compaction density and conductivity of the lithium iron manganese phosphate composite particles can be optimized, thereby having the best electrochemical performance and cycle performance. In a specific embodiment, the number of layers N of the lithium iron manganese phosphate coating layer can be but not limited to 6, 7, 8, 9, 10.

[0031] In an embodiment, the molar ratio of manganese to iron in the lithium manganese iron phosphate particles is (0-8): (10-2). Within the range of the molar ratio of manganese to iron in the lithium manganese iron phosphate particles provided in this embodiment, the molar ratio of manganese to iron in the positive electrode material formed by coating can be 6:4, so that the positive electrode material has the best comprehensive properties such as conductivity, compaction density and energy density. In a specific embodiment, the molar ratio of manganese phosphate to lithium phosphate can be but is not limited to (0-1): 10, (1-2): 9, (2-3): 8, (3-4): 7, (4-5): 6, (5-6): 5, (6-7): 4, (7-8): 3, 8:2.

[0032] In the embodiment, the molar ratio of manganese to iron in the polyphosphate positive electrode material is 6:4, that is, in the polyphosphate positive electrode material formed by the lithium manganese iron phosphate core and the N-layer lithium manganese iron phosphate coating layer, the molar ratio of manganese to iron is 6:4. This molar ratio can make the conductive performance, compaction density, energy density and other comprehensive properties of the positive electrode material reach the best at the same time. If it is higher than this molar ratio, the discharge efficiency and compaction density of the polyphosphate positive electrode material are easily reduced, and if it is lower than this molar ratio, the electrochemical properties such as energy density of the polyphosphate positive electrode material are easily reduced.

[0033] In an embodiment, the particle size of the lithium iron manganese phosphate composite particles satisfies: 2μm≤D50≤10μm. Within the particle size range of the lithium iron manganese phosphate composite particles provided in this embodiment, not only the compaction density of the polyphosphate positive electrode material can be improved, but also the electrochemical properties such as the conductivity and energy density of the polyphosphate positive electrode material can be improved. In a specific embodiment, the particle size of the lithium iron manganese phosphate composite particles can be, but is not limited to, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm.

[0034] In an embodiment, the thickness of the carbon coating layer is 1-3 nm. Within the thickness range of the carbon coating layer provided in this embodiment, the conductivity of the polyphosphate positive electrode material can be effectively improved, and the proportion of the manganese iron phosphate lithium composite particles in the positive electrode material can be ensured, so that the electrochemical performance of the composite material is not easily reduced. In a specific embodiment, the thickness of the carbon coating layer can be, but is not limited to, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm.

[0035] In an embodiment, the number of layers of the lithium iron manganese phosphate coating layer is N=8, that is, the lithium iron manganese phosphate composite particles include a lithium iron manganese phosphate core and 8 layers of lithium iron manganese phosphate coating layers, which are radially from the inside to the outside: the first lithium iron manganese phosphate coating layer, the second lithium iron manganese phosphate coating layer, the third lithium iron manganese phosphate coating layer, the fourth lithium iron manganese phosphate coating layer, the fifth lithium iron manganese phosphate coating layer, the sixth lithium iron manganese phosphate coating layer, the seventh lithium iron manganese phosphate coating layer and the eighth lithium iron manganese phosphate coating layer. Among them, the molar ratio of manganese to iron in the lithium iron manganese phosphate core and each layer of the lithium iron manganese phosphate coating layer is (0-0.005): 10, (1-1.005): 9, (2-2.005): 8, (3-3.005): 7, (4-4.005): 6, (5-5.005): 5, (6-6.005): 4, (7-7.005): 3, (8-8.005): 2 from the inside to the outside in the radial direction. The molar ratio of manganese to iron in the lithium iron manganese phosphate core and each layer of the lithium iron manganese phosphate coating layer provided in this embodiment increases radially from the inside to the outside, that is, the manganese content increases radially from the inside to the outside. As the manganese content increases, the conductivity decreases. Therefore, the coating structure of the polyphosphate positive electrode material places the lithium iron manganese phosphate particles with high manganese content and poor conductivity in the outer layer, which can shorten the lithium ion transmission distance and improve the conductivity.

[0036] In a specific embodiment, the molar ratio of manganese to iron in the lithium iron manganese phosphate core and each layer of lithium iron manganese phosphate coating is 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 from the inside to the outside in the radial direction. This embodiment can ensure that the molar ratio of manganese and iron in the positive electrode material including the lithium iron manganese phosphate core and 8 layers of lithium iron manganese phosphate coating is 6:4, so that the polyphosphate positive electrode material has the best comprehensive performance such as conductivity, compaction density and energy density.

[0037] In the embodiment, the radius of the lithium iron manganese phosphate core is 320-360nm; the thickness of each layer of lithium iron manganese phosphate coating layer is 280nm-320nm, 240nm-280nm, 200nm-240nm, 160nm-200nm, 120nm-160nm, 2080nm-3120nm, 2000nm-3200nm, 320nm-800nm ​​from the inside to the outside in the radial direction. Within the radius of the lithium iron manganese phosphate core provided by the lithium in this embodiment and the thickness of each layer of lithium iron manganese phosphate coating layer, the particle size of the lithium iron manganese phosphate composite particles formed by coating can be within the range of 2-10μm, thereby improving the compaction density of the polyphosphate positive electrode material, and can also improve the electrochemical properties such as the conductivity and energy density of the polyphosphate positive electrode material.

[0038] In the embodiment, the radius of the lithium iron manganese phosphate core is 320-360nm; the thickness of each layer of lithium iron manganese phosphate coating layer is 280nm-320nm, 240nm-280nm, 200nm-240nm, 160nm-200nm, 120nm-160nm, 80nm-120nm, 500nm-800nm, 320nm-800nm ​​from the inside to the outside in the radial direction. Within the radius of the lithium iron manganese phosphate core provided by the lithium in this embodiment and the thickness of each layer of lithium iron manganese phosphate coating layer, the particle size of the lithium iron manganese phosphate composite particles formed by coating can be within the range of 2-10μm, thereby improving the compaction density of the polyphosphate positive electrode material, and can also improve the electrochemical properties such as the conductivity and energy density of the polyphosphate positive electrode material.

[0039] In an embodiment, the particle size range of the lithium iron manganese phosphate particles in the lithium iron manganese phosphate core is 300nm≤D50≤340nm; the particle size range of the lithium iron manganese phosphate particles in each layer of the lithium iron manganese phosphate coating layer is 280nm≤D50≤320nm, 240nm≤D50≤280nm, 200nm≤D50≤240nm, 160nm≤D50≤200nm, 120nm≤D50≤160nm, 80nm≤D50≤120nm, 50nm≤D50≤80nm, and 20nm≤D50≤50nm from the inside to the outside in the radial direction. In the particle size range of the lithium iron manganese phosphate core and the lithium iron manganese phosphate particles in each layer of the lithium iron manganese phosphate coating provided in this embodiment, the particle size of the core of the lithium iron manganese phosphate composite particles and the lithium iron manganese phosphate particles in each layer are decreased radially from the inside to the outside, which can significantly improve the density of the internal filling of the composite particles and improve the compaction density of the positive electrode material. In an embodiment, the lithium iron manganese phosphate composite particles include a lithium iron manganese phosphate core and 8 layers of lithium iron manganese phosphate coating layers, and the mass ratio of the lithium iron manganese phosphate core and the lithium iron manganese phosphate in each layer of the lithium iron manganese phosphate coating layer is (1-1.005): (1-1.005): (1-1.005): (1-1.005): (1-1.005): (1-1.005): (5-5.005): (8-8.005) from the inside to the outside in the radial direction. Within the mass ratio range of lithium manganese iron phosphate of the 8 layers of lithium manganese iron phosphate coating provided in this embodiment, the thickness of each layer of lithium manganese iron phosphate coating can be ensured to be appropriate, the bonding between each layer of lithium manganese iron phosphate coating can be made tighter, the compaction density of the multi-phosphate positive electrode material can be improved, and the structural stability is good, so it has excellent electrochemical performance and cycle performance.

[0040] In a specific embodiment, the lithium iron manganese phosphate composite particles include a lithium iron manganese phosphate core and 8 layers of lithium iron manganese phosphate coating layers, and the mass ratio of the lithium iron manganese phosphate in the lithium iron manganese phosphate core and each layer of the lithium iron manganese phosphate coating layer is 1:1:1:1:1:1:1:5:8 from the inside to the outside in the radial direction. The lithium iron manganese phosphate mass ratio of the 8 layers of lithium iron manganese phosphate coating layers provided in this embodiment can ensure that the thickness of each lithium iron manganese phosphate coating layer is appropriate, and each layer of the lithium iron manganese phosphate coating layer can be most closely bonded, and the multi-phosphate positive electrode material has a high compaction density, thereby having good structural stability and excellent electrochemical performance and cycle performance.

[0041] In an embodiment, the lithium iron manganese phosphate composite particles include a lithium iron manganese phosphate core and 8 layers of lithium iron manganese phosphate coating layers, and the mass ratio of the lithium iron manganese phosphate in the lithium iron manganese phosphate core and each layer of the lithium iron manganese phosphate coating layer is (1-1.005) from the inside to the outside in the radial direction: (1-1.005): (1-1.005): (1-1.005): (1-1.005): (1-1.005): (1-1.005): (13-13.005): (20-20.005): (1-1.005). Within the mass ratio range of the lithium iron manganese phosphate in the 8 layers of lithium iron manganese phosphate coating layers provided in this embodiment, it can be ensured that the thickness of each layer of the lithium iron manganese phosphate coating layer is appropriate, the bonding between each layer of the lithium iron manganese phosphate coating layer can be made tighter, and the compaction density of the polyphosphate positive electrode material can be improved, so that the structural stability is good, and therefore it has excellent electrochemical performance and cycle performance.

[0042] In a specific embodiment, the lithium iron manganese phosphate composite particles include a lithium iron manganese phosphate core and 8 layers of lithium iron manganese phosphate coating layers, and the mass ratio of the lithium iron manganese phosphate in the lithium iron manganese phosphate core and each layer of the lithium iron manganese phosphate coating layer is 1:1:1:1:1:1:13:20:1 from the inside to the outside in the radial direction. The lithium iron manganese phosphate mass ratio of the 8 layers of lithium iron manganese phosphate coating layers provided in this embodiment can ensure that the thickness of each lithium iron manganese phosphate coating layer is appropriate, and each layer of the lithium iron manganese phosphate coating layer can be most closely bonded, and the multi-phosphate positive electrode material has a high compaction density, thereby having good structural stability and excellent electrochemical performance and cycle performance.

[0043] In the embodiment, a carbon protective layer is provided on the surface of the lithium iron manganese phosphate particles in the lithium iron manganese phosphate core and each layer of the lithium iron manganese phosphate coating layer. The thickness of the carbon protective layer is less than 1nm. In this embodiment, by providing a carbon protective layer with a thickness of less than 1nm on the surface of the lithium iron manganese phosphate particles in the lithium iron manganese phosphate core and each layer of the lithium iron manganese phosphate coating layer, manganese iron can be protected from oxidation, thereby improving the stability of the lithium iron manganese phosphate.

[0044] A second aspect of the present application provides a method for preparing a polyphosphate positive electrode material, comprising the following steps:

[0045] S10: preparing an ferromanganese phosphate core, and coating N layers of ferromanganese phosphate coating layers on the surface of the ferromanganese phosphate core to obtain ferromanganese phosphate composite particles;

[0046] S20: mixing and dissolving the manganese iron phosphate composite particles and the lithium source, performing a reaction treatment, and then performing a drying treatment to obtain manganese iron lithium phosphate composite particles;

[0047] S30: coating a carbon coating layer on the surface of the lithium manganese iron phosphate composite particles to obtain a polyphosphate positive electrode material.

[0048] The preparation method of the polynary phosphate positive electrode material provided in the embodiment of the present application, first prepares the ferromanganese phosphate kernel, and coats the surface of the ferromanganese phosphate kernel with N layers of ferromanganese phosphate coating to form ferromanganese phosphate composite particles, and by means of multi-layer coating, the particle size of the ferromanganese phosphate lithium composite particles can be increased, and the compaction density and conductivity of the ferromanganese phosphate lithium positive electrode material can be increased. Then the ferromanganese phosphate composite particles and the lithium source are mixed and dissolved, and the ferromanganese phosphate composite particles and the lithium source are reacted in a solution state, which can reduce the difficulty of synthesis, the required reaction temperature is low, and the reaction is more sufficient at the same time, the product conversion rate is high, and the obtained ferromanganese phosphate lithium composite particles have good uniformity, so that the stability and cycle performance of the ferromanganese phosphate lithium are better. In addition, the present application is to coat the surface of the ferromanganese phosphate kernel with N layers of ferromanganese phosphate coating to form ferromanganese phosphate composite particles, and then synthesize with the lithium source to form ferromanganese phosphate lithium composite particles, which can further improve the compactness, compaction density, structural stability, etc. of the composite particles compared with the ferromanganese phosphate lithium particles directly formed by sintering the ferromanganese phosphate particles and the lithium source. Finally, a carbon coating layer is coated on the surface of the lithium manganese iron phosphate composite particles to further improve the conductivity of the lithium manganese iron phosphate positive electrode material, thereby further improving the electrochemical performance and cycle performance. In addition, the preparation method is simple in process, high in efficiency, low in cost, and suitable for industrial large-scale production.

[0049] In step S10, the method for preparing the ferromanganese phosphate core includes: mixing the iron source and the manganese source according to a molar ratio of the manganese source to the iron source of (0-0.005):10, and then performing a first sintering treatment to obtain the ferromanganese phosphate particle core. The iron source can be iron phosphate, and the manganese source can be manganese phosphate. The temperature of the first sintering treatment is 640-660°C, and the time is 5h-8h; further, the temperature of the first sintering treatment is 640-650°C, and the time is 7h-8h.

[0050] In an embodiment, the method for preparing a ferromanganese phosphate core further includes: sintering ferromanganese phosphate particles with a first carbon source, forming a carbon protective layer on the surface of the ferromanganese phosphate particles, and obtaining a ferromanganese phosphate particle core with a surface coated with a carbon protective layer. The first carbon source is added in an amount of 1-3wt%. Within the range of the added amount of the first carbon source provided in this embodiment, the thickness of the carbon protective layer can be controlled to be less than 1nm, which can protect the ferromanganese from oxidation, thereby improving the stability of the ferromanganese phosphate.

[0051] In an embodiment, the first carbon source includes at least one of sucrose, glucose, oxalic acid, salicylic acid, citric acid, tartaric acid, malic acid, glycine, ethylenediaminetetraacetic acid, and succinic acid. The first carbon sources provided in this embodiment can be converted into gaseous hydrocarbons during high-temperature sintering, and can be deposited on the surface of ferromanganese phosphate particles to form a carbon protective layer, which can improve the stability of ferromanganese phosphate particles.

[0052] The method for coating an N-layer ferromanganese phosphate coating layer on the surface of a ferromanganese phosphate core comprises: mixing the iron source and the manganese source and performing a second sintering treatment according to the molar ratio of the manganese source to the iron source of (1-1.005):9, (2-2.005):8, (3-3.005):7, (4-4.005):6, (5-5.005):5, (6-6.005):4, (7-7.005):3, (8-8.005):2, respectively, to obtain ferromanganese phosphate particles with increasing manganese and iron molar ratios;

[0053] After ferromanganese phosphate particles with different manganese-iron molar ratios are made into slurries, the slurries are coated on the surface of the ferromanganese phosphate core in sequence according to the rule that the manganese-iron molar ratio increases radially from inside to outside, forming N layers of ferromanganese phosphate coating layers.

[0054] In the embodiment, the temperature of the second sintering treatment is 590-610℃, 540-560℃, 520-530℃, 490-510℃, 460-480℃, 430-450℃, 390-410℃, 340-360℃, and the time is 5-8h; further, the temperature of the second sintering treatment is 590-600℃, 540-550℃, 520-525℃, 490-500℃, 460-470℃, 430-440℃, 390-400℃, 340-350℃, and the time is 6-8h. In this embodiment, the particle size of the manganese iron phosphate particles can be adjusted by controlling the temperature of the second sintering treatment, so that the manganese iron molar ratio of the manganese iron phosphate lithium particles is inversely proportional to the particle size.

[0055] In a specific embodiment, according to the molar ratio of manganese source to iron source of (1-1.005):9, the iron source and the manganese source are mixed and sintered at a temperature of 590-610 ° C for 5-8h to obtain manganese iron phosphate particles with a manganese iron molar ratio of (1-1.005):9; according to the molar ratio of manganese source to iron source of (2-2.005):8, the iron source and the manganese source are mixed and sintered at a temperature of 540-560 ° C for 5-8h to obtain a manganese iron molar ratio of (2-2.005):8 Manganese ferrophosphate particles; according to the molar ratio of manganese source to iron source being (3-3.005):7, the iron source and the manganese source are mixed and sintered at a temperature of 520-530°C for 5-8h to obtain manganese ferrophosphate particles with a manganese-iron molar ratio of (3-3.005):7; according to the molar ratio of manganese source to iron source being (4-4.005):6, the iron source and the manganese source are mixed and sintered at a temperature of 490-510°C for 5-8h to obtain a manganese-iron molar ratio of (4-4.005):6. Ferromanganese particles; according to the molar ratio of manganese source to iron source being (5-5.005):5, the iron source and the manganese source are mixed and sintered at a temperature of 460-480°C for 5-8h to obtain ferromanganese phosphate particles with a manganese-iron molar ratio of (5-5.005):5; according to the molar ratio of manganese source to iron source being (6-6.005):4, the iron source and the manganese source are mixed and sintered at a temperature of 430-450°C for 5-8h to obtain ferromanganese phosphate with a manganese-iron molar ratio of (6-6.005):4 Particles; according to the molar ratio of manganese source to iron source of (7-7.005):3, the iron source and the manganese source are mixed and sintered at a temperature of 390-410°C for 5-8h to obtain ferromanganese phosphate particles with a manganese-iron molar ratio of (7-7.005):3; according to the molar ratio of manganese source to iron source of (8-8.005):2, the iron source and the manganese source are mixed and sintered at a temperature of 340-360°C for 5-8h to obtain ferromanganese phosphate particles with a manganese-iron molar ratio of (8-8.005):2. In the embodiment of the present application, as the manganese-iron molar ratio (manganese content) in the lithium ferromanganese phosphate particles increases, by gradually reducing the sintering temperature, ferromanganese phosphate particles whose particle size gradually decreases as the manganese content gradually increases can be formed, thereby achieving the purpose of shortening the lithium ion transmission distance.

[0056] In a specific embodiment, the method of coating the slurry on the surface of the ferromanganese phosphate core in sequence according to the rule that the manganese-iron molar ratio increases radially from the inside to the outside includes: using a spray drying method, spraying the ferromanganese phosphate slurry on the surface of the ferromanganese phosphate core in sequence according to the manganese-iron molar ratio from small to large, and forming the first ferromanganese phosphate coating layer, the second ferromanganese phosphate coating layer, the third ferromanganese phosphate coating layer... the N-1 ferromanganese phosphate coating layer, and the N ferromanganese phosphate coating layer in sequence.

[0057] In an embodiment, the method for coating an N-layer ferromanganese phosphate coating layer on the surface of a ferromanganese phosphate core further includes: sintering ferromanganese phosphate particles with different manganese-iron molar ratios with a second carbon source, respectively, forming a carbon protective layer on the surface of the ferromanganese phosphate particles, and obtaining ferromanganese phosphate particles with different manganese-iron molar ratios with a surface coated with a carbon protective layer. Wherein, the added mass percentage of the second carbon source is 1-3wt%. Within the added mass percentage range of the second carbon source provided in this embodiment, the thickness of the carbon protective layer can be controlled to be less than 1nm, and the ferromanganese can be protected from oxidation, thereby improving the stability of lithium ferromanganese phosphate.

[0058] In an embodiment, the second carbon source includes at least one of sucrose, glucose, oxalic acid, salicylic acid, citric acid, tartaric acid, malic acid, glycine, ethylenediaminetetraacetic acid, and succinic acid. The second carbon sources provided in this embodiment can be converted into gaseous hydrocarbons during high-temperature sintering, and can be deposited on the surface of ferromanganese phosphate particles to form a carbon protective layer, which can improve the stability of ferromanganese phosphate particles.

[0059] In step S20, the method of mixing and dissolving the ferromanganese phosphate composite particles and the lithium source and performing a reaction treatment includes: mixing and dissolving the ferromanganese phosphate composite particles, the lithium source and water according to the molar ratio of the ferromanganese phosphate composite particles and the lithium source of 1:1 and performing a reaction treatment. Wherein, the conditions for the reaction treatment include: a pH value of 6-9, a reaction temperature of 70-90°C, and a reaction time of 1-3h. Further, the conditions for the reaction treatment include: a pH value of 7-8, a reaction temperature of 75-85°C, and a reaction time of 2-3h. Within the range of reaction treatment conditions provided in this embodiment, the ferromanganese phosphate composite particles and the lithium source can fully react, the finished product yield is high, and the obtained ferromanganese phosphate lithium composite particles have good uniformity, so that the stability and cycle performance of the lithium iron manganese phosphate are optimized.

[0060] In an embodiment, the temperature of the drying process is 180-220° C. Further, the temperature of the drying process is 200-220° C.

[0061] In step S30, the method of coating the surface of the lithium iron manganese phosphate composite particles with a carbon coating layer includes: mixing the lithium iron manganese phosphate composite particles with a carbon source and then sintering them to obtain a lithium iron manganese phosphate positive electrode material. By mixing the lithium iron manganese phosphate composite particles with a carbon source and then sintering them, a carbon coating layer can be formed on the surface of the lithium iron manganese phosphate composite particles, which can not only fully fill the gaps between the particles, but also play a role in filling tightly, and can effectively improve the compaction density. In some embodiments, the added mass percentage of the carbon source is 15-20wt%. Within the added mass percentage range of the carbon source provided in this embodiment, a carbon coating layer with a suitable thickness can be formed, which can not only effectively improve the conductivity of the positive electrode material, but also ensure the proportion of the lithium iron manganese phosphate composite particles in the positive electrode material, thereby ensuring that the electrochemical performance of the composite material is good. In addition, the lithium iron manganese phosphate composite particles can be controlled to continue to grow, and the particle size of the particles can be maintained. In some embodiments, the conditions of the sintering treatment include: sintering for 5-8 hours in an inert atmosphere at a temperature of 650-750°C. The inert atmosphere can specifically be nitrogen or argon. Sintering within the range of conditions for the first sintering process provided in this embodiment can generate a stable carbon coating layer.

[0062] In an embodiment, the carbon source includes at least one of sucrose, glucose, oxalic acid, salicylic acid, citric acid, tartaric acid, malic acid, glycine, ethylenediaminetetraacetic acid, and succinic acid. The carbon sources provided in this embodiment can be converted into gaseous hydrocarbons during high-temperature sintering, and can be deposited on the surface of the lithium manganese iron phosphate composite particles to form a carbon coating layer, which can improve the stability and conductivity of the lithium manganese iron phosphate composite particles.

[0063] A third aspect of an embodiment of the present application provides a secondary battery, wherein the positive electrode material of the secondary battery includes the polyphosphate positive electrode material provided in the present application, or includes the polyphosphate positive electrode material prepared by the preparation method provided in the present application.

[0064] The secondary battery provided in the embodiment of the present application contains the polyphosphate positive electrode material of the present application. The polyphosphate positive electrode material has high electrochemical properties such as energy density, conductivity, compaction density, safety, and stability, thereby improving the electrochemical performance of the secondary battery.

[0065] The following describes the invention in conjunction with specific embodiments.

[0066] Examples 1-3 of the present application provide positive electrode materials and methods for preparing the same.

[0067] Example 1

[0068] The present embodiment provides a multi-phosphate positive electrode material, including lithium iron manganese phosphate composite particles and a carbon coating layer coated on the surface of the lithium iron manganese phosphate composite particles, the lithium iron manganese phosphate composite particles including a lithium iron manganese phosphate core and 8 layers of lithium iron manganese phosphate coating layers coated on the surface of the lithium iron manganese phosphate core;

[0069] Among them, the molar ratio of manganese to iron in the lithium iron manganese phosphate core is 0:10, and the molar ratio of manganese to iron in each layer of the lithium iron manganese phosphate coating layer is 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2 from the inside to the outside in the radial direction; the particle size of the manganese iron phosphate particles in the lithium iron manganese phosphate core is 300-340nm, and the particle size of the manganese iron phosphate particles in each layer of the lithium iron manganese phosphate coating layer is 280-320nm, 240-280nm, 200-240nm, 160-200nm, 120-160nm, 80-120nm, 50 -80nm, 20-50nm; the radius of the lithium iron manganese phosphate inner core is 320-360nm, and the thickness of each layer of the lithium iron manganese phosphate coating layer is 280nm-320nm, 240nm-280nm, 200nm-240nm, 160nm-200nm, 120nm-160nm, 80nm-120nm, 500nm-800nm, 320nm-800nm ​​along the radial direction from inside to outside; the thickness of the carbon coating layer is 1-3nm; the thickness of the carbon protective layer is <1nm; the particle size of the lithium iron manganese phosphate composite particles is 2.2-4.3μm.

[0070] The method for preparing the polyphosphate positive electrode material provided in this embodiment comprises the following steps:

[0071] S10: providing manganese phosphate and iron phosphate, wherein the molar ratio of manganese phosphate to iron phosphate is 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2, and the mass ratio of each ratio is 1:1:1:1:1:1:1:5:8, mixing the manganese phosphate and iron phosphate of each ratio into a raw material component, and then adding 2g of carbon source per 100g of the raw material component to form a mixed material, and mixing the manganese phosphate and iron phosphate. The mixtures with molar ratios of 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2 are calcined at 650°C, 600°C, 550°C, 530°C, 500°C, 470°C, 440°C, 400°C, and 350°C for 8h to obtain ferromanganese phosphate particles with a carbon protective layer having a manganese-iron molar ratio of 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2, respectively;

[0072] S20: using sand milling technology, preparing ferromanganese phosphate particles with manganese-iron molar ratios of 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2 into slurry, using ferromanganese phosphate particles with a carbon protective layer having a manganese-iron molar ratio of 0:10 as the core, and coating the slurry on the surface of the core in order of manganese-iron molar ratio from small to large by spray drying to obtain ferromanganese phosphate composite particles;

[0073] S30: according to the molar ratio of manganese iron phosphate composite particles to lithium carbonate being 1:1, 500 g of manganese iron phosphate composite particles and 75 g of lithium carbonate are placed in a stirring tank, and then 5 L of water is added for heating and stirring treatment, wherein the temperature of the heating and stirring treatment is 70-90° C., the time is 3 hours, and the pH value is 6-9. After the reaction is completed, the slurry is transported to a sand mill for pulverization treatment, and then spray-dried at a temperature of 180-220° C. to obtain manganese iron phosphate lithium composite particles;

[0074] S40: adding 20 g of carbon source per 100 g of lithium manganese iron phosphate composite particles, mixing the lithium manganese iron phosphate composite particles and the carbon source, and sintering them at 650° C. for 8 h to form a carbon coating layer, thereby obtaining a lithium manganese iron phosphate positive electrode material.

[0075] Example 2

[0076] The present embodiment provides a multi-phosphate positive electrode material, including lithium iron manganese phosphate composite particles and a carbon coating layer coated on the surface of the lithium iron manganese phosphate composite particles, the lithium iron manganese phosphate composite particles including a lithium iron manganese phosphate core and 8 layers of lithium iron manganese phosphate coating layers coated on the surface of the lithium iron manganese phosphate core;

[0077] The molar ratio of manganese to iron in the lithium iron manganese phosphate core is 0:10, and the molar ratio of manganese to iron in each layer of the lithium iron manganese phosphate coating layer is 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2 from the inside to the outside in the radial direction; the particle size of the manganese phosphate iron particles in the lithium iron manganese phosphate core is 300-340nm, and the particle size of the manganese phosphate iron particles in each layer of the lithium iron manganese phosphate coating layer is 280-320nm, 240-280nm, 200-240nm, 160-200nm, 120-160nm, 80-120nm, 50-80 nm, 20-50nm; the radius of the lithium iron manganese phosphate core is 320-360nm; the thickness of each layer of the lithium iron manganese phosphate coating is 280nm-320nm, 240nm-280nm, 200nm-240nm, 160nm-200nm, 120nm-160nm, 2080nm-3120nm, 2000nm-3200nm, 320nm-800nm ​​along the radial direction from inside to outside; the thickness of the carbon coating layer is 1-3nm; the thickness of the carbon protective layer is <1nm; the particle size of the lithium iron manganese phosphate composite particles is 5.4-8.3μm.

[0078] The method for preparing the polyphosphate positive electrode material provided in this embodiment comprises the following steps:

[0079] S10: providing manganese phosphate and iron phosphate, wherein the molar ratio of manganese phosphate to iron phosphate is 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2, and the mass ratio of each ratio is 1:1:1:1:1:1:13:20:1, mixing the manganese phosphate and iron phosphate of each ratio into a raw material component, and then adding 2g of carbon source per 100g of the raw material component to form a mixed material, and mixing the manganese phosphate and iron phosphate into a raw material component; Mixtures with molar ratios of iron of 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2 are calcined at 650°C, 600°C, 550°C, 530°C, 500°C, 470°C, 440°C, 400°C, and 350°C for 8 hours to obtain ferromanganese phosphate particles with a carbon protective layer having a manganese-iron molar ratio of 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2, respectively;

[0080] S20: using sand milling technology, preparing ferromanganese phosphate particles with manganese-iron molar ratios of 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2 into slurry, using ferromanganese phosphate particles with a carbon protective layer having a manganese-iron molar ratio of 0:10 as the core, and coating the slurry on the surface of the core in order of manganese-iron molar ratio from small to large by spray drying to obtain ferromanganese phosphate composite particles;

[0081] S30: according to the molar ratio of manganese iron phosphate composite particles to lithium carbonate being 1:1, 500 g of manganese iron phosphate composite particles and 75 g of lithium carbonate are placed in a stirring tank, and then 5 L of water is added for heating and stirring treatment, wherein the temperature of the heating and stirring treatment is 70-90° C., the time is 3 hours, and the pH value is 6-9. After the reaction is completed, the slurry is transported to a sand mill for pulverization treatment, and then spray-dried at a temperature of 180-220° C. to obtain manganese iron phosphate lithium composite particles;

[0082] S40: adding 20 g of carbon source per 100 g of lithium manganese iron phosphate composite particles, mixing the lithium manganese iron phosphate composite particles and the carbon source, and sintering them at 650° C. for 8 h to form a carbon coating layer, thereby obtaining a lithium manganese iron phosphate positive electrode material.

[0083] Example 3

[0084] The present embodiment provides a multi-phosphate positive electrode material, including lithium iron manganese phosphate composite particles and a carbon coating layer coated on the surface of the lithium iron manganese phosphate composite particles, the lithium iron manganese phosphate composite particles including a lithium iron manganese phosphate core and 8 layers of lithium iron manganese phosphate coating layers coated on the surface of the lithium iron manganese phosphate core;

[0085] Among them, the molar ratio of manganese to iron in the lithium iron manganese phosphate core is 0:10, and the molar ratio of manganese to iron in each layer of the lithium iron manganese phosphate coating layer is 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2 from the inside to the outside in the radial direction; the particle size of the manganese iron phosphate particles in the lithium iron manganese phosphate core is 300-340nm, and the particle size of the manganese iron phosphate particles in each layer of the lithium iron manganese phosphate coating layer is 280-320nm, 240-280nm, 200-240nm, 160-200nm, 120-160nm, 80-120nm, 50 -80nm, 20-50nm; the radius of the lithium iron manganese phosphate inner core is 320-360nm, and the thickness of each layer of the lithium iron manganese phosphate coating layer is 280nm-320nm, 240nm-280nm, 200nm-240nm, 160nm-200nm, 120nm-160nm, 80nm-120nm, 500nm-800nm, 320nm-800nm ​​along the radial direction from inside to outside; the thickness of the carbon coating layer is 1-3nm; the thickness of the carbon protective layer is <1nm; the particle size of the lithium iron manganese phosphate composite particles is 2.2-4.3μm.

[0086] The method for preparing the polyphosphate positive electrode material provided in this embodiment comprises the following steps:

[0087] S10: providing manganese phosphate and iron phosphate, wherein the molar ratio of manganese phosphate to iron phosphate is 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2, and the mass ratio of each ratio is 1:1:1:1:1:1:1:5:8, mixing the manganese phosphate and iron phosphate of each ratio into a raw material component, and then adding 2g of carbon source per 100g of the raw material component to form a mixed material, and mixing the manganese phosphate and iron phosphate. The mixtures with molar ratios of 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2 are calcined at 650°C, 600°C, 550°C, 530°C, 500°C, 470°C, 440°C, 400°C, and 350°C for 8h to obtain ferromanganese phosphate particles with a carbon protective layer having a manganese-iron molar ratio of 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2, respectively;

[0088] S20: using sand milling technology, preparing ferromanganese phosphate particles with manganese-iron molar ratios of 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2 into slurry, using ferromanganese phosphate particles with a carbon protective layer having a manganese-iron molar ratio of 0:10 as the core, and coating the slurry on the surface of the core in order of manganese-iron molar ratio from small to large by spray drying to obtain ferromanganese phosphate composite particles;

[0089] S30: according to the molar ratio of manganese iron phosphate composite particles to lithium carbonate being 1:1, 500 g of manganese iron phosphate composite particles and 75 g of lithium carbonate are placed in a stirring tank, and then 5 L of water is added for heating and stirring treatment, wherein the temperature of the heating and stirring treatment is 70-90° C., the time is 3 hours, and the pH value is 6-9. After the reaction is completed, the slurry is transported to a sand mill for pulverization treatment, and then spray-dried at a temperature of 180-220° C. to obtain manganese iron phosphate lithium composite particles;

[0090] S40: adding 20 g of carbon source per 100 g of lithium manganese iron phosphate composite particles, mixing the lithium manganese iron phosphate composite particles and the carbon source, and sintering them at 700° C. for 8 h to form a carbon coating layer, thereby obtaining a lithium manganese iron phosphate positive electrode material.

[0091] Comparative Example 1

[0092] This comparative example provides a polyphosphate positive electrode material, including lithium manganese iron phosphate particles and a carbon coating layer coated on the surface of the lithium manganese iron phosphate particles; wherein the manganese to iron molar ratio of the lithium manganese iron phosphate particles is 6:4, the particle size is 3.4-4.7μm, and the thickness of the carbon coating layer is 1-3nm.

[0093] The preparation method of the polyphosphate positive electrode material provided in this comparative example comprises the following steps:

[0094] S10: providing iron phosphate, manganese phosphate and lithium carbonate;

[0095] S20: mixing iron phosphate, manganese phosphate and lithium carbonate in a molar ratio of 6:4 and sintering the mixture at 800° C. for 12 hours to obtain lithium iron manganese phosphate particles;

[0096] S30: adding 20 g of carbon source per 100 g of lithium manganese iron phosphate particles, mixing the lithium manganese iron phosphate particles and the carbon source, and sintering them at 700° C. for 8 hours to form a carbon coating layer, thereby obtaining a lithium manganese iron phosphate positive electrode material.

[0097] Comparative Example 2

[0098] This comparative example provides a polyphosphate positive electrode material, including lithium iron manganese phosphate composite particles and a carbon coating layer coated on the surface of the lithium iron manganese phosphate composite particles; the lithium iron manganese phosphate composite particles include a lithium iron manganese phosphate core and 8 layers of lithium iron manganese phosphate coating layers coated on the surface of the lithium iron manganese phosphate core;

[0099] Among them, the manganese and iron molar ratios of the lithium iron manganese phosphate core and the 8 layers of lithium iron manganese phosphate coating layers are both 6:4; the particle size of the manganese iron phosphate particles in the lithium iron manganese phosphate core is 300-340nm, and the particle size of the manganese iron phosphate particles in each layer of the lithium iron manganese phosphate coating layer is 280-320nm, 240-280nm, 200-240nm, 160-200nm, 120-160nm, 80-120nm, 50-80nm, and 20-50nm from the inside to the outside along the radial direction; the thickness of the carbon coating layer is 1-3nm; the thickness of the carbon protective layer is <1nm; the particle size of the lithium iron manganese phosphate composite particles is 2.2-4.3μm.

[0100] The preparation method of the polyphosphate positive electrode material provided in this comparative example comprises the following steps:

[0101] S10: providing manganese phosphate and iron phosphate, mixing the manganese phosphate and iron phosphate into a raw material component according to a manganese-iron molar ratio of 6:4, then adding 2g of carbon source per 100g of the raw material component to mix the raw material component with the carbon source to form a mixed material, measuring the mixed material according to a mass ratio of 1:1:1:1:1:1:1:5:8, and roasting the mixed material at temperatures of 650°C, 600°C, 550°C, 530°C, 500°C, 470°C, 440°C, 400°C, and 350°C for 8h, respectively, to obtain 9 kinds of manganese phosphate iron particles with carbon protective layers of different particle sizes;

[0102] S20: Using the largest ferromanganese phosphate particles as the core, the other 8 ferromanganese phosphate particles with carbon protective layers of different particle sizes are prepared into slurry by sand milling technology, and the slurry is coated on the surface of the core in descending order of particle size by spray drying to obtain manganese iron phosphate lithium composite particles;

[0103] S30: according to the molar ratio of ferromanganese phosphate composite particles to lithium carbonate being 1:1, 500 g of ferromanganese phosphate composite particles and 75 g of lithium carbonate are placed in a stirring tank, and then 5 L of water is added for heating and stirring treatment, wherein the temperature of the heating and stirring treatment is 70-90° C., the time is 3 hours, and the pH value is 6-9. After the reaction is completed, the slurry is transported to a sand mill for pulverization treatment, and then spray-dried at a temperature of 180-220° C. to obtain lithium ferromanganese phosphate particles;

[0104] S40: adding 20 g of carbon source per 100 g of lithium manganese iron phosphate composite particles, mixing the lithium manganese iron phosphate composite particles and the carbon source, and sintering them at 650° C. for 8 h to form a carbon coating layer, thereby obtaining a lithium manganese iron phosphate positive electrode material.

[0105] Comparative Example 3

[0106] This comparative example provides a polyphosphate positive electrode material, including lithium iron manganese phosphate composite particles and a carbon coating layer coated on the surface of the lithium iron manganese phosphate composite particles; the lithium iron manganese phosphate composite particles include a lithium iron manganese phosphate core and 8 layers of lithium iron manganese phosphate coating layers coated on the surface of the lithium iron manganese phosphate core;

[0107] Among them, the molar ratio of manganese and iron in the lithium iron manganese phosphate core is 8:2, and the molar ratio of manganese and iron in each of the 8 layers of lithium iron manganese phosphate coating layers is 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, and 1:9 from the inside to the outside along the radial direction; the particle size of the manganese iron phosphate particles in the lithium iron manganese phosphate core is 300-340nm, and the particle size of the manganese iron phosphate particles in each layer of the lithium iron manganese phosphate coating layer is 280-320nm, 240-280nm, 200-240nm, 160-200nm, 120-160nm, 80-120nm, 50-80nm, and 20-50nm from the inside to the outside along the radial direction; the thickness of the carbon coating layer is 1-3nm; the thickness of the carbon protective layer is <1nm; the particle size of the lithium iron manganese phosphate composite particles is 2.2-4.3μm.

[0108] The preparation method of the polyphosphate positive electrode material provided in this comparative example comprises the following steps:

[0109] S10: providing manganese phosphate and iron phosphate, wherein the molar ratio of manganese phosphate to iron phosphate is 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2, and the mass ratio of each ratio is 1:1:1:1:1:1:1:5:8, mixing the manganese phosphate and iron phosphate of each ratio into a raw material component, and then adding 2g of carbon source per 100g of the raw material component to form a mixed material, and mixing the manganese phosphate and iron phosphate. The mixtures with molar ratios of 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2 are calcined at 350°C, 400°C, 440°C, 470°C, 500°C, 530°C, 550°C, 600°C, and 650°C for 8h to obtain ferromanganese phosphate particles with a carbon protective layer having a manganese-iron molar ratio of 0:10, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, and 8:2, respectively;

[0110] S20: Using the largest ferromanganese phosphate particles as the core, the other 8 ferromanganese phosphate particles with carbon protective layers of different particle sizes are prepared into slurry by sand milling technology, and the slurry is coated on the surface of the core in descending order of particle size by spray drying to obtain manganese iron phosphate lithium composite particles;

[0111] S30: according to the molar ratio of manganese iron phosphate composite particles to lithium carbonate being 1:1, 500 g of manganese iron phosphate composite particles and 75 g of lithium carbonate are placed in a stirring tank, and then 5 L of water is added for heating and stirring treatment, wherein the temperature of the heating and stirring treatment is 70-90° C., the time is 3 hours, and the pH value is 6-9. After the reaction is completed, the slurry is transported to a sand mill for pulverization treatment, and then spray-dried at a temperature of 180-220° C. to obtain manganese iron phosphate lithium composite particles;

[0112] S40: adding 20 g of carbon source per 100 g of lithium manganese iron phosphate composite particles, mixing the lithium manganese iron phosphate composite particles and the carbon source, and sintering them at 650° C. for 8 h to form a carbon coating layer, thereby obtaining a lithium manganese iron phosphate positive electrode material.

[0113] Related performance test analysis:

[0114] 1. Powder compression test: Weigh 1 g of the finished polyphosphate positive electrode materials provided in Examples 1-3 and Comparative Examples 1-2, respectively, and use a 3T pressure sensor to test the compaction density at a pressure of 10 MPa as shown in Table 1.

[0115] Table 1

[0116]

[0117] 2. Battery performance test: Using the polyphosphate positive electrode material particles provided in the above Examples 1-3 and Comparative Examples 1-2, a battery was assembled as follows:

[0118] Preparation of positive electrode sheet: Mix the polyphosphate positive electrode material, SP (conductive carbon black), PVDF (polyvinylidene fluoride) and NMP (N-methylpyrrolidone) in a mass ratio of 93.5:2.5:4:100 with a ball mill mixer for 2 hours to obtain a polyphosphate positive electrode slurry; add the prepared polyphosphate positive electrode slurry to the aluminum foil, evenly scrape it with a scraper, dry it at 130°C, and then roll it to obtain a positive electrode sheet.

[0119] Battery assembly process: The prepared positive electrode is attached to the positive electrode metal shell with conductive adhesive, a metal lithium sheet is used as the negative electrode, a Celgard 2400 microporous membrane is used as the separator, and a 1.0 mol / L LiPF6 solution is used as the electrolyte. The solvent of the electrolyte is a mixture of ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1. The button batteries are assembled in a glove box.

[0120] The electrochemical performance of the button cell was tested using a LAND electrochemical tester, with a charge termination voltage of 4.2 V and a discharge termination voltage of 2.0 V. The test results are shown in Table 2 below.

[0121] Table 2

[0122]

[0123] It can be seen from the above test results that the multi-phosphate positive electrode materials provided in Examples 1-3 of the present application, since the manganese-iron molar ratio of the inner core and each layer of the lithium iron manganese phosphate coating layer increases radially from the inside to the outside, is equivalent to placing the lithium iron manganese phosphate with a low manganese content in the inner layer and the lithium iron manganese phosphate with a high manganese content in the outer layer, that is, the lithium iron manganese phosphate with high conductivity is placed in the inner layer, and the lithium iron manganese phosphate with low conductivity is placed in the outer layer. Not only does it have good structural stability and high compaction density, but it also achieves the placement of lithium iron manganese phosphate particles with poor conductivity in the outer layer, shortening the transmission distance of lithium ions and improving conductivity. Therefore, the multi-phosphate positive electrode materials provided in the examples of the present application have excellent electrical properties, volume energy density and other electrochemical properties.

[0124] Compared with Examples 1-3, the lithium iron manganese phosphate particles contained in the multi-phosphate positive electrode material provided in Comparative Example 1 are not a single-core multi-layer coating structure, and their compaction density is significantly lower than that of Examples 1-3 of the present application, and their structural stability is poor. At the same time, the lithium iron manganese phosphate particles are directly formed by sintering a mixture of iron source, manganese source, and lithium source, which makes the lithium iron manganese phosphate particles have low electrical conductivity. Therefore, the overall electrical properties such as volume energy density and discharge of the battery provided in Comparative Example 1 are significantly lower than those of Examples 1-3.

[0125] The lithium iron manganese phosphate composite particles contained in the multi-phosphate positive electrode material provided in Comparative Example 2 have the same manganese-iron molar ratio between the inner core and each layer of the lithium iron manganese phosphate coating layer, and the particle sizes of the manganese-iron phosphate particles in the inner core and each layer of the lithium iron manganese phosphate coating layer decrease radially from the inside to the outside. Although the compaction density can be made equivalent to that of the embodiment of the present application through multi-layer coating; however, since the lithium ion transmission distance of the lithium iron manganese phosphate particles sintered at high temperature becomes longer, the electrical performance is reduced, and the manganese-iron molar ratio between the inner core and each layer of the lithium iron manganese phosphate coating layer is the same, the electrical conductivity of the lithium iron manganese phosphate composite particles is relatively low. Therefore, the overall electrical performance such as the volume energy density and discharge of the battery provided in Comparative Example 2 is significantly lower than that of Examples 1-3.

[0126] The lithium iron manganese phosphate composite particles contained in the multi-phosphate positive electrode material provided in Comparative Example 3 have a manganese-iron molar ratio of the inner core and each layer of the lithium iron manganese phosphate coating layer that decreases radially from the inside to the outside, which is equivalent to placing the lithium iron manganese phosphate with a high manganese content in the inner layer and the lithium iron manganese phosphate with a low manganese content in the outer layer, that is, the lithium iron manganese phosphate with low electrical conductivity is placed in the inner layer, and the lithium iron manganese phosphate with high conductivity is placed in the outer layer. Since the lithium ion transmission distance is increased during high-temperature sintering, although the lithium iron manganese phosphate particles with low manganese content coated in the outer layer have a small particle size and excellent electrical properties, the upper limit of the electrical performance of the lithium iron manganese phosphate is not high, and the electrical performance influence caused by the poor conductivity of the lithium iron manganese phosphate particles with high manganese content placed in the inner layer cannot be solved. Therefore, the overall electrical performance of the battery provided in Comparative Example 3, such as volume energy density and discharge, is significantly lower than that of Examples 1-3.

[0127] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A polyphosphate positive electrode material, characterized in that: The polyphosphate positive electrode material comprises a lithium iron manganese phosphate composite particle and a carbon coating layer coated on the surface of the lithium iron manganese phosphate composite particle, and the lithium iron manganese phosphate composite particle comprises a lithium iron manganese phosphate core and an N-layer lithium iron manganese phosphate coating layer coated on the surface of the lithium iron manganese phosphate core; Wherein, the molar ratio of manganese to iron in the lithium iron manganese phosphate core and each layer of the lithium iron manganese phosphate coating increases radially from the inside to the outside; the particle size of the lithium iron manganese phosphate particles in the lithium iron manganese phosphate core and each layer of the lithium iron manganese phosphate coating decreases radially from the inside to the outside, and N=an integer of 1-10; The molar ratio of manganese to iron in the lithium manganese iron phosphate particles is (0-8): (10-2); The particle size of the lithium manganese iron phosphate composite particles satisfies: 2μm ≤ D50 ≤ 10μm.

2. The polyphosphate positive electrode material according to claim 1, characterized in that The molar ratio of manganese to iron in the polyphosphate positive electrode material is 6:4; and / or N = 6-10; and / or The thickness of the carbon coating layer is 1-3 nm.

3. The polyphosphate positive electrode material according to claim 1, characterized in that N=8; The molar ratio of manganese to iron in the lithium manganese iron phosphate core is (0-0.005):10; the molar ratio of manganese to iron in each layer of the lithium manganese iron phosphate coating is (1-1.005):9, (2-2.005):8, (3-3.005):7, (4-4.005):6, (5-5.005):5, (6-6.005):4, (7-7.005):3, (8-8.005):2 from the inside to the outside in the radial direction; and / or The particle size range of the lithium iron manganese phosphate particles in the lithium iron manganese phosphate core is 300nm≤ D50 ≤340nm; the particle size range of the lithium iron manganese phosphate particles in each layer of the lithium iron manganese phosphate coating layer is 280nm≤ D50≤320nm, 240nm ≤ D50 ≤280nm, 200nm ≤ D50 ≤240nm, 160nm ≤ D50 ≤200nm, 120nm≤ D50 ≤160nm, 80nm ≤ D50 ≤120nm, 50nm ≤ D50 ≤80nm, and 20nm ≤ D50 ≤50nm from the inside to the outside in the radial direction.

4. The polyphosphate positive electrode material according to claim 3, characterized in that: The mass ratio of the lithium manganese iron phosphate in the lithium manganese iron phosphate core and each layer of the lithium manganese iron phosphate coating layer from inside to outside in the radial direction is (1-1.005): (1-1.005): (1-1.005): (1-1.005): (1-1.005): (1-1.005): (1-1.005): (1-1.005): (5-5.005): (8-8.005); or The mass ratio of the lithium manganese iron phosphate in the lithium manganese iron phosphate core and each layer of the lithium manganese iron phosphate coating is (1-1.005) from inside to outside in the radial direction: (1-1.005): (1-1.005): (1-1.005): (1-1.005): (1-1.005): (1-1.005): (13-13.005): (20-20.005): (1-1.005).

5. The polyphosphate positive electrode material according to claim 4, characterized in that The radius of the lithium iron manganese phosphate core is 320-360nm; the thickness of each layer of the lithium iron manganese phosphate coating layer is 280nm-320nm, 240nm-280nm, 200nm-240nm, 160nm-200nm, 120nm-160nm, 80nm-120nm, 500nm-800nm, 320nm-800nm ​​from the inside to the outside in the radial direction; or The radius of the lithium iron manganese phosphate core is 320-360nm; the thickness of each layer of the lithium iron manganese phosphate coating is 280nm-320nm, 240nm-280nm, 200nm-240nm, 160nm-200nm, 120nm-160nm, 2080nm-3120nm, 2000nm-3200nm, and 320nm-800nm ​​from the inside to the outside along the radial direction.

6. The polyphosphate positive electrode material according to any one of claims 1 to 5, characterized in that: A carbon protective layer is provided on the surface of the lithium iron manganese phosphate particles in the lithium iron manganese phosphate core and each layer of the lithium iron manganese phosphate coating layer.

7. The polyphosphate positive electrode material according to claim 6, characterized in that The thickness of the carbon protective layer is less than 1 nm.

8. A method for preparing a polyphosphate positive electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Preparing an ferromanganese phosphate core, and coating N layers of ferromanganese phosphate coating layers on the surface of the ferromanganese phosphate core to obtain ferromanganese phosphate composite particles; The manganese iron phosphate composite particles and a lithium source are mixed and dissolved, reacted, and then dried to obtain the manganese iron lithium phosphate composite particles; The carbon coating layer is coated on the surface of the lithium manganese iron phosphate composite particles to obtain the polyphosphate positive electrode material.

9. The method for preparing a polyphosphate positive electrode material according to claim 8, wherein the molar ratio of the manganese-iron phosphate composite particles to the lithium source is 1:1; and / or The reaction treatment conditions include: The pH value is 6-9, the reaction temperature is 70-90°C, and the reaction time is 1-3h; and / or The temperature of the drying process is 180-220°C.

10. The method for preparing the polyphosphate positive electrode material according to claim 8 or 9, wherein the method for coating the carbon coating layer on the surface of the lithium manganese iron phosphate composite particles comprises: The lithium manganese iron phosphate composite particles are mixed with a carbon source and then sintered to obtain a polyphosphate positive electrode material.

11. The method for preparing a polyphosphate positive electrode material according to claim 10, wherein the sintering conditions include: Sintering in an inert atmosphere at a temperature of 650-750°C for 5-8 hours; and / or The carbon source includes at least one of sucrose, glucose, oxalic acid, salicylic acid, citric acid, tartaric acid, malic acid, glycine, ethylenediaminetetraacetic acid, and succinic acid.

12. A secondary battery, characterized in that: The positive electrode material of the secondary battery includes the polyphosphate positive electrode material as described in any one of claims 1 to 7, or includes the polyphosphate positive electrode material prepared by the preparation method as described in any one of claims 8 to 11.

Citation Information

Patent Citations

  • Positive electrode material, positive electrode slurry, positive electrode plate and battery

    CN114204015A